Functional characterization of a Baculovirus fibroblast growth factor - Detvisitsakun, Chanitchote (Kansas State University, 2006)
Baculoviridae is the only known virus family that encodes genes with homology to vertebrate and invertebrate fibroblast growth factors (fgfs), key regulators of developmental processes affecting cell growth, differentiation, and motility. The role of viral fgfs during infection is not known. In this study, we investigated gene regulation and function of the Autographa californica M nucleopolyhedrovirus (AcMNPV) fgf during infection of permissive insect cells. We demonstrated that the AcMNPV fgf, vfgf, was transcribed as a 0.6-kb mRNA at early times post infection, but as part of a 1.4-kb bicistronic mRNA at late times. To determine its function, we examined common characteristics between vFGF and other well-characterized FGF homologs. vFGF had strong affinity to heparin, a property important for FGF signaling via an FGF receptor. vFGF was secreted into the extracellular fluid when expressed in insect cells, suggesting that it acts as an extracellular ligand. Finally, vFGF was able to stimulate chemokinesis of different types of insect cells. We also constructed a recombinant of AcMNPV lacking a functional vfgf and analyzed it in two insect cell lines. The kinetics of budded virus production were similar in the parental and vfgf-deficient viruses in two cell lines and at both high and low multiplicities of infection. In addition, we observed no obvious differences in the viral DNA synthesis and the protein kinetic profiles of cells infected with the mutant and parental viruses. Finally, coinfection of vfgf-containing and -deficient viruses and their passage for several generations did not reveal a consistent growth advantage for either virus. We propose that vFGF is the signal that directs the motility of uninfected tracheal or blood cells to infected tissues, enabling the virus to infect additional cells and spread systemically in the insect host. This proposal may explain a dispensable role for vfgf during virus infection in cell culture; nonetheless, we expect a distinct phenotypic difference between vfgf-deficient and vfgf-containing viruses during infection in the insect host.
Keywords: Baculoviruses; Fibroblast growth factors; Biology, Molecular (0307)